CGH, cDNA and Tissue Microarray Analyses Implicate FGFR2 Amplification in a Small Subset of Breast Tumors - Mervi Heiskanen; Juha Kononen; Maarit Bärlund; Joachim Torhorst; Guido Sauter; Anne Kallioniemi; Olli Kallioniemi (Analytical Cellular Pathology)
Multiple regions of the genome are often amplified during breast cancer development and progression, as evidenced in a number of published studies by comparative genomic hybridization (CGH). However, only relatively few target genes for such amplifications have been identified. Here, we indicate how small‐scale commercially available cDNA and CGH microarray formats combined with the tissue microarray technology enable rapid identification of putative amplification target genes as well as analysis of their clinical significance. According to CGH, the SUM‐52 breast cancer cell line harbors several high‐level DNA amplification sites, including the 10q26 chromosomal region where the fibroblast growth factor receptor 2 (FGFR2) gene has been localized. High level amplification of FGFR2 in SUM‐52 was identified using CGH analysis on a microarray of BAC clones. A cDNA microarray survey of 588 genes showed >40‐fold overexpression of FGFR2. Finally, a tissue microarray based FISH analysis of 750 uncultured primary breast cancers demonstrated in vivo amplification of the FGFR2 gene in about 1% of the tumors. In conclusion, three consecutive microarray (CGH, cDNA and tissue) experiments revealed high‐level amplification and overexpression of the FGFR2 in a breast cancer cell line, but only a low frequency of involvement in primary breast tumors. Applied to a genomic scale with larger arrays, this strategy should facilitate identification of the most important target genes for cytogenetic rearrangements, such as DNA amplification sites detected by conventional CGH. Figures on http://www.esacp.org/acp/2001/22‐4/heiskanen.htm